A decision support tool for monitoring rice area, yield, and climate change impacts on rice production in Cote d’Ivoire. Initial piloting activities - Murugesan, Deiveegan; Satapathy, Sushree; Akpoffo, Marius; Gatti, Luca; Maunahan, Aileen; Dossou-Yovo, Elliot; Holecz, Francesco; Mathieu, Renaud; Ouedraogo, Mathieu (2024)
Rice plays a vital role in the agricultural landscape of Ivory Coast in West Africa, serving as a keystone of the country's agricultural sector and food security, especially in the Bouake region, which significantly contributes to the country's rice production. With ongoing efforts in modernization, irrigation, and technological advancements, rice cultivation in the Bouake region continues to thrive, supporting local livelihoods and contributing to the nation's food security. To achieve sufficient rice productivity and promote sustainable agricultural practices, the Ivory Coast government has been actively taking many interventions, while monitoring rice areas and production estimates is crucial for designing/targeting interventions and for taking sound policy decisions. Transforming Agri-Food Systems in West and Central Africa (TAFS-WCA) is an CGIAR integrated regional initiative that aims to improve nutrition and food security within the context of climate change in West and Central Africa through nutritious, climate-adapted and market-driven food systems. As part of this initiative, Work Package 2 (Digital Agriculture) is implementing the Remote Sensing-based Information and Insurance for Crops in Emerging Economies (RIICE) tool (www.riice.org) , which is piloted in the Bouake region of Ivory Coast. This tool supports the government's endeavors to achieve rice self-sufficiency, and the pilot will aim to propose the implementation of this technology for monitoring rice production at national scale. This report presents the preliminary activities and initial outputs of the wet season 2023 over the Bouake region using RIICE technology, in collaboration with sarmap, Switzerland, AfricaRice, the Alliance of Bioversity International, CIAT, and local partners.